Analysis of quality of life of rectal cancer patients after transanal total mesorectal excision and laparoscopic total mesorectal excision: a retrospective cohort study - CHEN Jiayu, LI Yue, CHEN Fan, LI Yuxue, FENG Shidong, HUANG Qi, LI Dawei, LIAO Zhiwei (Zhongguo aizheng zazhi)
Background and purpose: There are few studies on the quality of life after transanal total mesorectal excision (TaTME) for rectal cancer, and there is a lack of evidence-based research. This study aimed to evaluate the impact of TaTME in comparison to laparoscopic total mesorectal excision (LaTME) on postoperative quality of life in patients. Methods: A retrospective analysis was conducted on clinical and pathological data from rectal cancer patients who underwent LaTME and TaTME between September 2019 and September 2022 at Renhe Hospital, Baoshan District, Shanghai, and Fudan University Shanghai Cancer Center. All the patients completed a set of validated questionnaires one year postoperatively, including the EORCT QLQ-C30, Low Anterior Resection Syndrome (LARS) score, International Prostate Symptom Score (IPSS), Generalized Anxiety Disorder-7 (GAD-7), and Patient Health Questionnaire-9 (PHQ-9). Comparative analysis of these survey results was performed.The study was approved by the Ethics Committee of Renhe Hospital, Baoshan District, Shanghai. The Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist was followed for this study. Results: A total of 39 patients in the TaTME group and 38 patients in the LaTME group were included. There were no statistically significant differences between two groups regarding demographic variables such as gender and age, as well as clinical factors including tumor distance from the anal verge, tumor stage, and preoperative neoadjuvant treatment protocols. Analysis of EORCT QLQ-C30 results indicated equivalent overall quality of life between the two groups; however, the TaTME group reported significantly more severe insomnia (P=0.020). No significant differences were observed in LARS severity or total scores between the groups, though the TaTME group demonstrated superior functional outcomes in terms of incontinence for liquid stools and clustering of stools (P=0.007, P=0.004). Additionally, both groups exhibited comparable results in IPSS, and levels of depression and anxiety. Conclusion: The findings suggest that TaTME and LaTME yield similar outcomes in terms of anal and urinary function, overall quality of life, and psychological health, indicating that it is a viable and safe alternative to LaTME in terms of postoperative quality of life.